Karakteristik Kepemimpinan Pendidikan Islam - Ulinnuha, Nur Raisah (Universitas Muhammadiyah Jember, 2019)
Leadership can be interpreted as a process of influencing and directing citizens or workers to do work according to their duties. The fact is that in Indonesia many leaders who are wrongfully caught buying and selling positions, corruption and so on. A leader must have a noble mind, because he will be a role model, he who will create opportunities and provide encouragement as well as input to its members. Like the Javanese language slogan from the father of education which is often promoted in the world of education Ing Ngarso Sung Tulodo, Ing Madyo Mangun Karso and Tut Wuri Handayani. In Islam, Allah has given examples of exemplary living examples namely the Prophet Muhammad who has the nature of siddiq, tabligh, trust and fathanah. The main types of Islamic education leadership include authoritarian leadership, free leadership and democratic leadership. While complementary Islamic education leadership types include charismatic leadership types, guardian leadership types, expert leader types, organizational and administrator leadership types, agitator leadership types.